Dietary eubiotics of microbial muramidase and glycan improve intestinal villi, ileum microbiota composition and production trait of broiler - Sungbo Cho; Shanmugam Suresh Kumar; Santiago Ramirez; Rolando Valientes; In Ho Kim (Journal of Animal Science and Biotechnology, 2024)
Abstract Background Optimal gut health is important to maximize growth performance and feed efficiency in broiler chickens. A total of 1,365 one-day-old male Ross 308 broiler chickens were randomly divided into 5 treatments groups with 21 replicates, 13 birds per replicate. The present research investigated effects of microbial muramidase or a precision glycan alone or in combination on growth performance, apparent total tract digestibility, total blood carotenoid content, intestinal villus length, meat quality and gut microbiota in broiler chickens. Treatments included: NC: negative control (basal diet group); PC: positive control (basal diet + 0.02% probiotics); MR: basal diet + 0.035% microbial muramidase; PG: basal diet + 0.1% precision glycan; and MRPG: basal diet + 0.025% MR + 0.1% PG, respectively. Results MRPG group increased the body weight gain and feed intake (P < 0.05) compared with NC group. Moreover, it significantly increased total serum carotenoid (P < 0.05) and MRPG altered the microbial diversity in ileum contents. The MRPG treatment group increased the abundance of the phylum Firmicutes, and family Lachnospiraceae, Ruminococcaceae, Oscillospiraceae, Lactobacillaceae, Peptostreptococcaceae and decreased the abundance of the phylum Campilobacterota, Bacteroidota and family Bacteroidaceae. Compared with the NC group, the chickens fed MRPG showed significantly increased in duodenum villus length at end the trial. Conclusion In this study, overall results showed that the synergetic effects of MR and PG showed enhancing growth performance, total serum carotenoid level and altering gut microbiota composition of broilers. The current research indicates that co-supplementation of MR and PG in broiler diets enhances intestinal health, consequently leading to an increased broiler production.